Area-to-Length Ratio: a significant predictor of nonunion following intramedullary nailing of comminuted femoral shaft fractures - Shi, Yi; Jiang, Wei; Wang, Anquan; Hua, Xingyi (Frontiers in Surgery, 2026)
BackgroundThe relationship between fragment characteristics and nonunion risk in comminuted femoral shaft fractures remains controversial. This study aimed to investigate the relationship between radiographic fragment features and fracture union outcomes to assist clinical assessment.Patients and methodsA retrospective analysis was conducted on 91 femoral shaft fractures from 89 patients. Patient demographics, injury characteristics, and radiographic parameters—including fragment size, displacement, gap area, nail-to-canal diameter ratio, and ALR (gap area/major fragment length)—were analyzed. Univariate and multivariate logistic regression were used to identify independent risk factors for nonunion.ResultsThe overall nonunion rate was 16.5% (15/91). Univariate analysis revealed that a larger gap area (OR = 1.004, P < 0.001) and a lower distal nail-to-canal diameter ratio (OR = 0.013, P = 0.023) were associated with nonunion. The novel ALR parameter demonstrated a strong association with nonunion (OR = 2.349, P < 0.001). In multivariate analysis, ALR remained an independent predictor (OR = 2.304, P < 0.001), while traditional factors like fragment size, displacement, and the nail-to-canal ratio were not significantly associated.ConclusionTraditional radiographic measures such as fragment length, width, Nail-to-canal ratio and absolute displacement did not show a significant association with healing outcome in our cohort. While the ALR is a significant predictor of nonunion in comminuted femoral shaft fractures, may assist in the early identification of cases at higher risk for nonunion, which could inform clinical vigilance regarding the potential need for more intensive management strategies.